Justice League. Vol. 1, Prisms - Bendis, Brian Michael (Justice League, 2022)
"Writer Brian Michael Bendis reunites with artist David Marquez for a new, star-studded Justice League featuring Batman, Superman, the Flash, Hawkgirl, Aquaman, Hippolyta, new DC powerhouse Naomi, and...is that Black Adam? Superman is leading the charge to reinvent the Justice League-and at the same time, a new, cosmic-powered threat arrives from Naomi's homeworld to rule the Earth! And as a backup story, dark days ahead for the new Justice League Dark. Zatanna and John Constantine take a road trip, only to discover horror around the bend as a friend-and sometimes foe-is reborn in fire! A legend is destroyed and another takes a terrible turn, as Merlin reveals the beginning of a new, blood-drenched plot for all humankind."--